Nurse perception on medication error in Intensive Care Unit - Mohamed Ariffin, Suzilawati; Ludin, Salizar; Ilias, Nurul Afida (Journal of Medical Biomedical and Applied Sciences, 2019)
Introduction: Medication error is incorrect or wrongful administration of medication that can cause harm to patient safety. The role of healthcare provider especially nurses is important in preventing the medication error. Objectives: To assess the nurse perception on medication error. Methods/Materials: A cross-sectional study was conducted among 65 nurses who work in Intensive Care Unit. A set of questionnaires distributed and data obtained were analyzed using SPSS for descriptive and inferential analysis. Result: Most participated respondents are female (N=61, 93.8%). The nurses agree on the importance to report medication error even no harm has resulted to the patient (98.4%), nurse manager should keep track of a nurse’s medication errors (96.9%) and medication-dispensing technology reduces medication error (95.4%). Important factors that potentially contribute to medication error were unclear verbal order (86.2%), look-alike sound-alike drugs (84.6%), and insufficient training (73.8%). The perception of medication error and factor contributed to medication error has a weak and negatively relationship (-0.179) and not correlated (p=0.077). The significant association was seen between demographic characteristics and nurses’ perception on medication error. Only education level seen associated with perception on medication error (p=0.01). Conclusion: Emphasizing the nurse understanding may reduce the incidence of medication error in ICU.